Gestão territorial e conflitos socioambientais no Parques Estadual dos Pirineus (GO) - Andrade, Edna de Araújo (2018)
This thesis had the objective to understand and configure the territorial management of the Pirineus State Park, in Goiás. It was based on the understanding that the analysis of the territory, including the process of appropriation of space, through the power relations, combined, among others, to the political, economic and social aspects, contain solid bases of explanatory character of the reality, in the scope of the management of protected areas. The methodological procedures included bibliographic research, and public documents; field work, and semi-structured interviews with expropriated landowners, residents of the surrounding area, state and municipal managers and technicians. The study integrates, essentially, investigations related to the used territory, which allowed to identify the interfaces that make up the societal processes, and the socioenvironmental conflicts. The territorial management of conservation units was conceived as a complex process that involves the context of a territory, with history, conflicts of interest, articulations and negotiations that go beyond the perspective of institutional management of legally established limits. In this conception, the study resulted in the systematized identification of the conflicts in the historical context and pointed out the relational feature that involves the process of occupation of the sorrounding area and the management of the protected area. The analyses indicated that the implementation of the park did not influence the territorial dynamics, and the management problems, such as the lack of a management plan, the precariousness of the physical structure and the lack of advisory council are representative elements for the emblematic framework that involves the use of the territory and the socioenvironmental conflicts. The territory of the park used for the Festa do Morro (Festival of the Hill), for pasture, for public use and other uses, denotes the multiplicity of territories, and shows that there were agreements and social interfaces that were strengthened and consolidated. Thus, the uses of the territory and the socioenvironmental conflicts lead to the interpretation that the various agents and actors participate, interfere and influence in the governmental management. In this broad and multidimensional perspective, the territorial management of the conservation unit was delineated.